PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA SUNGAI PINANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Nur Annisya; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the Sungai Pinang village Hulu Kuantan Kuantan Singingi Regency. This study aims to determine how the public participation in the implementation of infrastructure construction and to know what are the factors that influence public participation in the implementation of infrastructure construction. This study, entitled “Participation rate of society for implementation of construction infrastructure at Sungai Pinang Village Hulu Kuantan Subdisrtict Kuantan Singingi Regency”. The main problem in this research is how the public participation in the implementation of infrastructure construction at Sungai Pinang Village and what are the factors that influence public participation in the implementation of infrastructure construction at Sungai Pinang Village. The samples in this research is using random sampling. Amount of total population in 2015, which amounted to 274 families (KK), samples taken were 30 families (KK) which has represented the population redetermined criteria. The method used is quantitative method with a descriptive approach. Instrument filtering data used are observation, kuisioner and documentation. The results have generally been carried out by the researcher, the researcher can say that public participation in the implementation of infrastructure construction Sungai Pinang Village are low by category never participate are contributing donation totaling 19 respondents (63%), because they assume that all donation has been given by the government and the other reason is they are just hard to build his house let alone to donate donation to the construction. Factors that affect the implementation of infrastructure construction is low educational factors is 16 respondents (54%), and work factors is 15 respondents (50%). Education and employment factors are very influential because they are educated will definitely get the job also high, therefore their participation due to lower prioritize their personal work.Keywords: Participation, Community, Construction